Monkey me: and the new neighbor - Roland, Timothy (New York: Scholastic, 2014)
When Clyde gets excited, he turns into a monkey. His twin sister, Claudia, is always trying to calm him down, especially at school. The principal does not like a monkey loose in the building. But when Clyde and Claudia get a surprising new neighbor, Clyde will come closer than ever to being caught.